CEO characteristics and bank performance: Case of Vietnamese commercial banks - Nam Hai Pham (Cogent Economics & Finance, 2023)
The article was conducted to evaluate the impact of CEO characteristics on the performance of Vietnamese commercial banks. Variables representing the performance of commercial banks are return on total assets (ROA) and return on equity (ROE). Data was collected from 30 Vietnamese commercial banks from 2012-2020. By the regression methods of Pooled OLS, Fixed Effects Model (FE), Random Effects Model (RE), Feasible Generalized Least Squares (FGLS), the research results show that CEO duality and CEO age positively impact the performance of Vietnamese commercial banks. In contrast, the female CEO factor has a negative impact on ROE. In addition, the study did not find evidence of the impact of the CEO's financial background and the CEO tenure on the performance of Vietnamese commercial banks.
Keywords: C23; G20; G21; 330; Agency theory; Bank performance; CEO characteristics; Resource dependency theory; Stewardship theory; Vietnam